2021
DOI: 10.21597/jist.793731
|View full text |Cite
|
Sign up to set email alerts
|

Süt Kalitesi Üzerine İşletme Yapı ve Yönetimlerinin Etkileri

Abstract: ÖZET: Bu araştırma Erzurum'da faaliyet gösteren süt sığırcılığı işletmelerindeki ineklerden alınan süt örneklerinden belirlenen somatik hücre sayısı (SHS), elektriksel geçirgenlik, protein ve yağ değerleri ile bu işletmelerin bazı yapısal özellikleri; barınak, tipi, altlık tipi, sağım sistemi ve işletme büyüklüğü arasındaki ilişkilerin karşılaştırılması amaçlanmıştır. Araştırmada Erzurum'da faaliyet gösteren 8 adet ailesel tip ve 8 adet modern süt sığırcılığı işletmelerinden alınan çiğ süt örnekleri kullanılmı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The percentage of farms which has a milking parlor was 2.0% (Figure 2). In similar other research conducted in other regions of Türkiye, it was reported that the percentage of enterprises which used hand milking method was 96.5% in Van province (Bakır, 2002), 81.0% in Çayırlı county of Erzincan province (Özyürek et al, 2014), 78.4% in Kars province (Demir et al, 2014), 89.2% in Hınıs county of Erzurum province (Koçyiğit et al, 2016), 71.5% in Muş province, and 62.5% in Erzurum central cattle farms (Sarıalioğlu and Laçin, 2021). It can be deduced that hand milking method is more common in the Eastern part of Türkiye.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of farms which has a milking parlor was 2.0% (Figure 2). In similar other research conducted in other regions of Türkiye, it was reported that the percentage of enterprises which used hand milking method was 96.5% in Van province (Bakır, 2002), 81.0% in Çayırlı county of Erzincan province (Özyürek et al, 2014), 78.4% in Kars province (Demir et al, 2014), 89.2% in Hınıs county of Erzurum province (Koçyiğit et al, 2016), 71.5% in Muş province, and 62.5% in Erzurum central cattle farms (Sarıalioğlu and Laçin, 2021). It can be deduced that hand milking method is more common in the Eastern part of Türkiye.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, it was stated that milk quality and SCC obtained from modern farms were better than familial type farms. Therefore, it has been emphasized that there is a relationship between welfare and SCC (Sarıalioğlu & Laçin, 2021). The fact that there is no significant relationship between SCC and locomotion and social interaction is due to the similar scale and structure of the enterprises.…”
Section: Discussionmentioning
confidence: 99%